2019
DOI: 10.3389/fphys.2019.00979
|View full text |Cite
|
Sign up to set email alerts
|

Clarity and Confusion in the Development of Youth Aerobic Fitness

Abstract: Peak oxygen uptake ( ) is internationally recognized as the criterion measure of youth aerobic fitness, but flawed laboratory assessments and fallacious interpretations of peak in ratio with body mass have confused our understanding of the development of aerobic fitness. Moreover, the recent emergence of specious predictions of peak from performance tests and the promotion of spurious “clinical red flags” and cardiometabolic cut-points have confused our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
2
22
0
1
Order By: Relevance
“…Nevertheless, we also showed that higher VȮ 2peak scaled by BM was associated with better MC and lower BF% suggesting that the previous observations on the positive associations of MC with CRF and the modifying role of CRF in the associations between MC and BF% are largely influenced by body composition rather than peak aerobic power. 18,22 T A B L E 2 Associations of peak oxygen uptake (VȮ Although we found weak and statistically insignificant association between VȮ 2peak scaled by LM, MC, and BF%, we observed that W max scaled either by LM or BM was positively associated with MC. We also found a weak inverse association between W max scaled by LM and BF% in the PANIC Study, which is in contrast to the results with VȮ 2peak .…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Nevertheless, we also showed that higher VȮ 2peak scaled by BM was associated with better MC and lower BF% suggesting that the previous observations on the positive associations of MC with CRF and the modifying role of CRF in the associations between MC and BF% are largely influenced by body composition rather than peak aerobic power. 18,22 T A B L E 2 Associations of peak oxygen uptake (VȮ Although we found weak and statistically insignificant association between VȮ 2peak scaled by LM, MC, and BF%, we observed that W max scaled either by LM or BM was positively associated with MC. We also found a weak inverse association between W max scaled by LM and BF% in the PANIC Study, which is in contrast to the results with VȮ 2peak .…”
Section: Discussionmentioning
confidence: 59%
“…Our findings do not support previous findings on the positive associations of MC and CRF in children. 6 A reason for these divergent results is that previous studies have used body size and composition confounded measures of CRF, 16,18,22,31 such as 20-m shuttle run test 6 or VȮ 2peak scaled by BM, 13,14 while we utilized VȮ 2peak scaled by LM that is the preferred method to normalize CRF for body size and composition. 22 Furthermore, we found a weak and statistically insignificant relationship of VȮ 2peak scaled by LM to BF% while we observed a strong inverse association between VȮ 2peak scaled by BM and BF%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Third, the use of a ratio-scaled value of CRF (absolute VO 2 divided by body weight) may hamper the correct interpretation of the association between fitness and fatness. 59 In the case of the 20-m shuttle run test, participants have to carry their weight over a series of 20-m shuttle runs, which adversely affects performance in the heavier participants. 60 Nonetheless, we used an equation to estimate CRF that was validated without correcting the test performance by any anthropometric measure.…”
Section: Limitationsmentioning
confidence: 99%